IDENTIFIKASI DAN KARAKTERISASI UMBI KELADI TIKUS SEBAGAI ZAT ANTIOKSIDAN ALAMI - Sukardi . (Jurnal Gamma, 2011)
SukardiStaf Pengajar Jurusan Teknologi Hasil Pangan, Fakultas Pertanian-Peternakan, Universitas Muhammadiyah MalangAlamat Korespondensi : Joyogrand Blok A2 No 4 MalangEmail : sukardiumm@yahoo.co.idABSTRACTKeladi Tikus plant can be used as a herbal medicine that is the leaves and tubers. Keladi Tikusis believed to cure various diseases, especially cancer. Keladi Tikus contain ribosome inacting protein(RIP), antioxidants and substances antikurkumin (Yayat, 2008). Presumably this is an antioxidantcompound that causes taro potential in curing mice of cancer. In research conducted solvent extractionof ethyl acetate, ethanol and hexane to obtain the yield and antioxidant activity test. To determine thestability of antioxidants is heating, irradiation and oxidation of design used randomized block design(RAK) factorial. Research results indicate that the water content of tubers of taro flour rat that is10.74%. Sucrose content 0.38% hexane, ethyl acetate extract 0.65% and 1.63% ethanol extract.Taro extract the most active mice obtained from the ethanol extract and its active compounds areflavonoids. Old heating, sunshine and light significantly affected the stability of antioxidant activity.The highest damage occurred in pengeruh pemaasan and then the sun light is very small while theeffect on antioxidant activity declined.Key words : keladi tikus, extraction, stability antioxidants